The Effects of Vitamin D on Gentamicin-Induced Acute Kidney Injury in Experimental Rat Model. (15th June 2013) - Hur, Ender; Garip, Alev; Camyar, Asuman; Ilgun, Sibel; Ozisik, Melih; Tuna, Sena; Olukman, Murat; Narli Ozdemir, Zehra; Yildirim Sozmen, Eser; Sen, Sait; Akcicek, Fehmi; Duman, Soner
Abstract : Introduction . Acute kidney injury (AKI) pathogenesis is complex. Findings of gentamicin nephrotoxicity are seen in 30% of the AKI patients. Vitamin D has proven to be effective on renin expression, inflammatory response, oxidative stress, apoptosis, and atherosclerosis. We aimed to investigate the effect of vitamin D in an experimental rat model of gentamicin-induced AKI. Methods . Thirty nonuremic Wistar albino rats were divided into 3 groups: Control group, 1 mL saline intramuscular (im) daily; Genta group, gentamicin 100 mg/kg/day (im); Genta + vitamin D, gentamicin 100 mg/kg/day (im) in addition to 1 α, 25 (OH)2 D3 0.4 mcg/kg/day subcutaneously for 8 days. Blood pressures and 24-hour urine were measured. Blood urea and creatinine levels and urine tubular injury markers were measured. Renal histology was semiquantitatively assessed. Results . Urea, creatinine and urine neutrophil gelatinase-associated lipocalin, and kidney injury molecule-1 were all increased in Genta group indicating AKI model. Systolic blood pressure decreased, but urine volume and glutathione increased in Genta + Vit D group compared to Control group. Histological scores indicating tubular injury increased in Genta and Genta + Vit D groups. Conclusions . Vitamin D does not seem to be effective on histological findings although it has some beneficial effects via RAS system and a promising effect on antioxidant system.